Studi Penggunaan Plastik Polypropylene pada Campuran Asphalt Concrete-Wearing Course - Lie Ing Tan; Wildan Reza Pahlevi (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2020)
The quality of implementation, drainage, materials that do not meet the standards, and overloaded from the specified class of roads are the main causes of road damage. Thus violations and negligence both in the implementation or maintenance of the road can cause a lot of traffic accidents, damage to vehicles, and various things that can disrupt the comfort and safety of drivers or pedestrians. The purpose of this study was to evaluate the effect of polypropylene plastic as an additive in the Asphalt Concrete-Wearing Course (AC-WC) layer. The use of polypropylene waste used as an additive is around 2.5%; 3.5%; 4.5%; and 5.5% of the asphalt weight. Based on the results of the analysis it was concluded that the mixture of AC-WC with the addition of polypropylene plastic experienced increased stability and decreased melting. Polypropylene plastic which can be used based on the five Marshall test parameters with the highest value of stability and lowest melting is 4.5% of the weight of asphalt.